D–A–A′-type asymmetric small molecules based on triphenylamine-diketopyrrolopyrrole/5, 6-difluoro-2, 1, 3-benzothiadiazole backbone for organic photovoltaic materials. (27th July 2020) - Yin, Lunxiang; Yuan, Qingqing; Li, Yanqin
Abstract : Five novel asymmetric OSMs are designed and synthesized with a tuned terminal group and central core, and the effect of their structure on their photoelectrical properties are investigated. Abstract : Five novel asymmetric D–A–A′-type small molecules (SMs) consisting of a triphenylamine (TPA)-diketopyrrolopyrrole (DPP)/5, 6-difluoro-2, 1, 3-benzothiadiazole (BT) conjugated backbone with different terminal groups were designed and synthesized successfully. First, the ethynyl-functionalized thiophene was introduced to BT-based SMs with the terminal electron-withdrawing groups 3-phthalimide and 3-ethylrhodanineto, namely BT-1 and BT-2, respectively. Next, to improve their optical absorption, the DPP unit was used as the central unit to replace the BT unit and the electron-withdrawing groups 3-phthalimide, 3-ethylrhodanine, and 1, 3-indandione acted as the terminal moiety, giving DPP-1, DPP-2 and DPP-3, respectively. It is worth mentioning that the absorption of DPP-based compounds extended to the near-infrared region, achieving materials with absorption band edges over 850 nm and a narrow bandgap of up to 1.35 eV. The BT-2 -based device showed the highest open-circuit voltage ( V oc ) of 1.03 V among the molecules due to a deeper HOMO level. Also, besides being a donor material, the BT-based molecules showed potential as acceptor materials. Although the PCE was still low, the bifunctional properties of these materials, which can be used as both donor and acceptor, should be investigated. Among these synthetic SMs, the DPP-1 -based device exhibited the best PCE of 4.21% due to its most appropriate energy level and moderate bandgap.